Experimental Mechanics of Solids and Structures - Oyo, Yang (Darya Ganj : Amiga Press, 2021)
Experimental Mechanics of Solids and Structures also replaces mechanical testing in a larger context: firstly, that of the experimental model, with its own hypotheses. The mechanics are a physical science, since it deals with the study of physical phenomena. The mechanics are the body of knowledge that deals with the relationships between forces and the motion of points through space, including the material space. This book is devoted to the basic variations principles of mechanics. This book presents the classical tools in the experimental approach to mechanical engineering.
Includes bibliography and index.
Keywords: Solid mechanics; Optical; mechanics